ANALISIS PENGARUH ENVIRONMENT COST DISCLOSURE (ECD) DAN INDONESIAN ENVIRONMENT REPORTING (IER) TERHADAP SUSTAINABILITY REPORTING (Studi pada Perusahaan Manufaktur yang Terdaftar di Jakarta Islamic Index (JII) Tahun 2020-2022) - Anggi Setya Yulyan; Ruslan Abdul Ghofur; Yulistia Devi; Nanda Audia (Jurnal Akuntansi dan Audit Syariah)
The aims of this research is to determine the influence of Environmental Cost Disclosure (ECD) and Indonesian Environmental Reporting (IER) on Sustainability Reporting (SR) in manufacturing companies registered with JII for the 2020-2022 period, and how sustainable reporting for a companyinIslamic perspective. This type of research is quantitative in the form of secondary data and uses purposive sampling techniques for panel data. The sample used is 10 companies registered with JII from 2020 to 2022. The data used are annual reports and sustainability reports which are accessed at www.idx.co.id. Data were processed using SPSS Version 25. Descriptive tests, classical assumption tests, multiple linear regression analysis tests and hypothesis tests were used for analysis. The research results show that Environmental Cost Disclosure (ECD) partially has no effect on Sustainability Reporting (SR), Indonesian Environmental Reporting (IER) partially has a negative effect on Sustainability Reporting (SR). And simultaneously Environmental Cost Disclosure (ECD) and Indonesian Environmental Reporting (IER) have a positive effect on Sustainability Reporting (SR).